The Usefulness of Zakat Infak Funds in the Sang Surya Scholarship Program - Rifki Hanif Setiawan; Artika Salsabila; Olyvia Azzahra; Zahra Zanzabila (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2025)
Zakat is a mandatory practice carried out by Muslims in accordance with the provisions of Islamic religious teachings (must enter Nishob and haul), zakat is included in the 3rd pillar of Islam is done after prayer. The difference with Infak is that anyone can do it by donating part of their wealth for good. Infak and shodaqah zakat funds are managed by the Amil Zakat Agency or the legal Amil Zakat Institution from the Ministry of Religion of the Republic of Indonesia. One of the Zakat and Infak funds managed by BAZ/LAZ can be used for scholarship programs, to improve the status of the underprivileged through education. The service office of Lemabaga Amil Zakat Infak and Shodaqah Muhammadiyah (Lazismu) Unmuh Babel has a program, namely the Sang Surya Scholarship. This research aims to find out the usefulness of zakat and infak funds managed by KL Lazismu Unmuh Babel for the Sang Surya Scholarship program. The research method used was qualitative descriptive, the data source used primary data in the form of questionnaire results and in-depth interviews, while secondary data was obtained from documents about the scholarship of the solar KL Lazismu Unmuh Babel. This research produced; Zakat and infak funds managed by KL Lazismu Unmuh Babel provide benefits for students, parents and the campus, because with this scholarship students are helped to pay their tuition fees/SK/UKT to continue their studies and can improve their degree through education.